The Meaning of Child’s Mental Illness for Mother - Dian Natalia; Yohanis F. La Kahija (Faculty of Psychology, Diponegoro University, 2013)
The aim of this research was to understand and described what the meaning of child mental illness for mother. Method used in this research was qualitative research study with phenomenological approach. Subjects consisted of two mothers who had child experienced mental illness and still in a home medication. The result of this research showed that mother experience rejection in the beginning they know their children had mental illness. The rejection consist of anger, stress, tired off, and feel ashamed of child. Beside that, subject felt worried about child future. Both subject do adaptation to encounter these negative feeling. The adaptation developed by subjects was problem-solved coping, emotional coping, and positive perception.Another family member attitude, subject internal value, and how environment react affected how subject gave a meaning on child mental illness.